HYGIENIC ASSESSMENT OF WORKING CONDITIONS OF INFECTIONISTS DOCTORS (ON THE EXAMPLE OF THE REPUBLIC OF KARAKALPAKSTAN) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The work of medical workers is one of the important, complex and responsible types of human activity. The result of the activity of medical workers - the health of the population, is largely determined by working conditions and their health. The problem of maintaining the health of the working population is the basis of the social policy of the state. The Constitution of the Republic of Uzbekistan and labor legislation provide for the rights of employees to safe working conditions, to receive information about the existing risk of damage to health, and the employer's obligation to ensure the safety of employees and inform them about the existing risk of damage to health in the workplace, as well as to carry out measures to preserve and strengthen the health of workers. The above fully applies to medical workers. [4]